Clinical case: experience in the treatment of hyperplastic gingivitis in a patient with poor oral hygiene - P. A. Voronin; A. G. Prityko; A. E. Kazakova; V. A. Voronin; I. A. Nikolskaya (Эндодонтия Today, 2025)
INTRODUCTION. The fibrous form of hyperplastic gingivitis is a complex condition characterized by chronic inflammation of the gingiva accompanied by fibrotic tissue transformation. Conservative treatment approaches are often insufficient, and surgical intervention is required to restore both esthetics and function. AIM. To evaluate the effectiveness of a stepwise treatment approach for the fibrous form of hyperplastic gingivitis in a patient with a long-standing disease history and inadequate personal oral hygiene. MATERIALS AND METHODS. A clinical case study was conducted involving a 30-year-old patient diagnosed with a moderate form of fibrous hyperplastic gingivitis. Treatment was carried out in sequential phases, including etiological therapy aimed at reducing inflammation through professional oral hygiene procedures, patient education, and motivation. The surgical phase involved gingivectomy and reshaping of the gingival contour on both jaws. The supportive phase included regular follow-up visits, repeated professional hygiene sessions, and instruction in the use of an oral irrigator, interdental brushes, and dental floss. RESULTS. Following the conservative phase, a reduction in inflammatory symptoms was observed, although significant gingival hypertrophy persisted. Surgical intervention led to a stable esthetic outcome in the maxilla and partial stabilization in the mandible. At the 11-month follow-up, a recurrence of inflammation was noted in the mandibular anterior region, particularly in areas challenging to clean, underscoring the need for consistent oral hygiene habits. CONCLUSIONS. Surgical correction of fibrotically altered gingiva is essential to achieving stable clinical results, as conservative treatment alone is typically ineffective in such cases. The success of therapy is directly dependent on the patient’s adherence to oral hygiene instructions and commitment to routine professional maintenance. Periodontal patients, even in remission, require systematic monitoring at intervals of no more than three months to maintain treatment outcomes and prevent recurrence.